Evaluation of The Personnel Information System of The Human Resources Development Agency for Transportation Using the Hot Fit-Model - Handayani, Citra; Prihandoko, Prihandoko (Journal of World Science, 2023)
In this modern era, it is undeniable that information technology is one of the main resources in an organization that plays an important role in increasing competitiveness and providing optimal service. Every government organization tries to apply information technology to increase service effectiveness and efficiency. This study aims to prove the extent to which the BPSDMP (Human Resources Development Agency for Transportation) staffing information system uses the HOT-FIT Model approach. This study uses a research approach with model evaluation methods. The research involved 62 employees at the Ministry of Transportation's BPSDMP. The data analysis technique used in this study is to use validity test, reliability test, classic assumption test and research hypothesis test. The results show that the BPSDMP Personnel Information System is dominated by human factors with a correlation coefficient value of 0.636, then an organizational correlation coefficient of 0.619 and a technology correlation coefficient of 0.589. In this study, the components of human, organizational and technological factors, together with net benefits, have a coefficient of determination of 56.4%.